Free Food at Work: A Concept Analysis. (June 2021) - Horton Dias, Cynthia; Dawson, Robin M.; Abshire, Demetrius A.; Harris, Diane; Wirth, Michael D.
Background: Employees who spend substantial amounts of time in a workplace away from home are likely to acquire and consume food during work hours. Reportedly, free food at work is a common occurrence in various workplace settings such as business offices and hospitals. Little is known about the nutritional quality, prevalence, or health impact of free food at work. Furthermore, free food at work as a theoretical concept has not been previously analyzed or defined, but it is necessary to differentiate free food from other food sources in the workplace. Methods: A concept analysis of free food at work was conducted using the 8-step Walker and Avant framework. A literature review in June and July 2020 provided the basis to delineate the concept and identify its defining attributes including antecedents, consequences, and empirical referents. Findings: Free food at work is defined as food that is available for consumption in the workplace at no financial cost to employees. Critical attributes of free food at work include nutritional value, quantity, frequency, and location within the workplace. Antecedents are sources and reasons for free food provision. Consequences include influence on consumption, behaviors, attitudes, emotions, and health outcomes. Additional measurable aspects of the concept and implications are discussed. Conclusion/Application to Professional Practice: The concept of free food at work was analyzed; defining attributes and empirical referents were discussed and presented in a conceptual model to encourage further study and theory development. Identifying the health impact of free food at work is an issue requiring consideration for workplace health-promoting programs.